KINERJA KARYAWAN HOUSEKEEPING DI HOTEL UNIGRAHA PANGKALAN KERINCI - Elni Ramadani; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aim to determine the peformance of employe in hotel Housekeeping Unigraha Pangkalan Kerinci base an to determine the most dominant peformance in Unigraha pangkalan KerinciThis researce uses quantitative method to process the data obtained in the field through interviews on the field all the information gathered and learned and to become a unified whole (Kusuma dan Sugono.2000) data collection techniques observation, interview questionnaireBased on the research that ha been done in the hotel housekeeping employee performance unigraha pangkalan kerinci with the questionnaire so are agreedKeywords : performance, discipline